2008
DOI: 10.1001/archsurg.2007.56
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Cardiorespiratory and Stress Factors in Esophageal Surgery Using Robot-Assisted Thoracoscopic or Open Thoracic Approach

Abstract: The robot-assisted approach is associated with improved intraoperative cardiopulmonary function and seems to be a less stressful technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The present study shows that RARP accelerates surgical stress recovery along the neuroendocrine system. Our results are confirmed by an experimental study that compared the stress response to robotic technology during thoracoscopic mobilization and anastomosis of the esophagus vs. the conventional open approach [19] . As a theory, RRP increased the hyper inflammatory response followed by cell-mediated immunosuppression which triggered higher stress levels along the HPA axis ( Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The present study shows that RARP accelerates surgical stress recovery along the neuroendocrine system. Our results are confirmed by an experimental study that compared the stress response to robotic technology during thoracoscopic mobilization and anastomosis of the esophagus vs. the conventional open approach [19] . As a theory, RRP increased the hyper inflammatory response followed by cell-mediated immunosuppression which triggered higher stress levels along the HPA axis ( Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Measurement of surgical stress is used in people for evaluation of anesthetic protocols . Similarly, measurement of surgical stress is used for the evaluation of surgical techniques . In 1 study, 2 different approaches for lumbar spine surgery were compared.…”
mentioning
confidence: 99%
“…One experimental study showed that the robot‐assisted thoracic approach was associated with improved intraoperative cardiopulmonary function and less stress compared with the open thoracic approach 41. The study used 12 pigs and evaluated hemodynamics (central venous pressure, pulmonary vascular resistance, cardiac output, and blood gas values), substance P and cortisol levels.…”
Section: Comparison With Conventional Proceduresmentioning
confidence: 99%